Novel molecular markers of cardiovascular disease risk in type 2 diabetes mellitus - Giglio, Rosaria Vincenza; Stoian, Anca Pantea; Haluzik, Martin; Pafili, Kalliopi; Patti, Angelo Maria; Rizvi, Ali Abbas; Ciaccio, Marcello; Papanas, Nikolaos; Rizzo, Manfredi (Biochimica et biophysica acta. Molecular basis of disease, 2021)
Diabetes represents the leading risk factor for the development of cardiovascular disease (CVD). Chronic hyperglycemia and/or acute post-prandial changes in blood glucose determine an increase in reactive oxygen species (ROS), which play a fundamental role in endothelial dysfunction and in the nuclear transport of pro-atherogenic transcription factors that activate the "inflammasome". In addition, the glycemic alteration favors the formation and stabilization of atherosclerotic plaque through the mechanism of non-enzymatic glycation of different molecules, with the establishment of the so-called "advanced glycosylation end products" (AGE). Laboratory information provided by the level of biomarkers could make a quantitative and qualitative contribution to the clinical process of screening, prediction, prevention, diagnosis, prognosis and monitoring of cardiovascular (CV) risk linked to diabetes. This review describes the importance of specific biomarkers, with particular focus on novel ones, for stratifying and management of diabetes CV risk.
Keywords: Glycation; Inflammation; krevní glukóza; reaktivní formy kyslíku; lidé; Diabetes Mellitus, Type 2; diabetes mellitus 2. typu; Type 2 diabetes mellitus; Cardiovascular Diseases; Reactive Oxygen Species; Blood Glucose; Humans; Novel biomarkers; biologické markery; Cardiovascular risk; rizikové faktory; Biomarkers; Risk Factors; kardiovaskulární nemoci; Oxidative stress